4-1BB Agonists: Multi-Potent Potentiators of Tumor Immunity - Bartkowiak, Todd; Curran, Michael A. (Frontiers in Oncology, 2015)
Immunotherapy is a rapidly expanding field of oncology aimed at targeting, not the tumor itself, but the immune system combating the cancerous lesion. Of the many approaches currently under study to boost anti-tumor immune responses; modulation of immune co-receptors on lymphocytes in the tumor microenvironment has thus far proven to be the most effective. Antibody blockade of the T cell co-inhibitory receptor cytotoxic T lymphocyte antigen-4 (CTLA-4) has become the first FDA approved immune checkpoint blockade, however, tumor infiltrating lymphocytes express a diverse array of additional stimulatory and inhibitory co-receptors which can be targeted to boost tumor immunity. Among these, the co-stimulatory receptor 4-1BB (CD137/TNFSF9) possesses an unequaled capacity for both activation and pro-inflammatory polarization of anti-tumor lymphocytes. . While functional studies of 4-1BB have focused on its prominent role in augmenting cytotoxic CD8 T cells, 4-1BB can also modulate the activity of CD4 T cells, B cells, natural killer cells, monocytes, macrophages, and dendritic cells. 4-1BB’s expression on both T cells and antigen presenting cells, coupled with its capacity to promote survival, expansion, and enhanced effector function of activated T cells, has made it an alluring target for tumor immunotherapy. In contrast to immune checkpoint blocking antibodies, 4-1BB agonists can both potentiate anti-tumor and anti-viral immunity, while at the same time ameliorating autoimmune disease. Despite this, 4-1BB agonists can trigger high grade liver inflammation which has slowed their clinical development. In this review, we discuss how the underlying immunobiology of 4-1BB activation suggests the potential for therapeutically synergistic combination strategies in which immune adverse events can be minimized.